Clinical and haemodynamic risk factors associated with discrepancies in lower limb length with capillary malformations: data from the national paediatric French cohort CONAPE. (20th January 2018) - Samimi, M.; Durieux‐Verde, M.; Caille, A.; Mazereeuw‐Hautier, J.; Boccara, O.; Martin, L.; Chiaverini, C.; Eschard, C.; Beneton, N.; Vabres, P.; Balguerie, X.; Plantin, P.; et al.
Summary: Background: Genetics discoveries have allowed for a better understanding of capillary malformations (CMs) associated with overgrowth syndrome. However, molecular analyses are still not easy to perform or interpret. Other analytical methods are needed. Objectives: To identify clinical and haemodynamic factors associated with leg length discrepancy (LLD) in children with CMs of the lower limbs. Methods: Data were obtained from the multicentre French national cohort CONAPE (COhorte Nationale d'enfants atteints d'Angiome Plan de membrE inférieur), from children aged 2–12 years old with CMs of the lower limbs. Clinical characteristics were prospectively collected. Haemodynamic factors were measured by an sonographer who calculated the arterial blood flow (ABF) in both lower limbs. An ABF difference ≥ 50% between the two lower limbs was considered relevant. LLD ≥ 2% was determined by the same radiologist on centralized radiographs. Results: We analysed data at baseline for 96 children. The mean ± SD age was 5·6 ± 3·1 years; 49 (51%) were male; and 14 (15%) showed LLD. In total, 32 patients (33%) had venous anomalies, 13 (14%) lymphatic anomalies and in one child a diagnosis of Parkes Weber syndrome was made. Only an increased circumference above the knee was more frequent with than without LLD (43% vs. 13%, P = 0·02). In all, 10/79 patients (13%) showed a difference in ABF ≥ 50%: four had LLD. The frequency of differences in ABF ≥ 50% was greater with than without LLD [33% ( n = 4/12) vs. 9% ( n = 6/67), P = 0·04]. Conclusions: ABF measured by Duplex ultrasonography is a simple, low‐cost and noninvasive complementary examination for help in detecting LLD, with a difference of ≥ 50% possibly associated. Abstract : What's already known about this topic? Capillary malformations (CMs) might be associated with venous, lymphatic or arteriovenous anomalies or with overgrowth syndrome such as leg length discrepancy (LLD). Molecular analyses have allowed for better understanding. What does this study add? In children with CMs of the lower limbs the frequency of differences in arterial blood flow ≥ 50% between the two limbs was greater with than without LLD. Respond to this article